Lake–atmosphere interactions at Alqueva reservoir: a case study in the summer of 2014. Issue 1 (1st January 2017) - Potes, M.; Salgado, R.; Costa, M. J.; Morais, M.; Bortoli, D.; Kostadinov, I.; Mammarella, I.
ABSTRACT: The study of lake–atmosphere interactions was the main purpose of a 2014 summer experiment at Alqueva reservoir in Portugal. Near-surface fluxes of momentum, heat and mass [water vapour (H2 O) and carbon dioxide (CO2 )] were obtained with the new Campbell Scientific's IRGASON Integrated Open-Path CO2 /H2 O Gas Analyser and 3D Sonic Anemometer between 2 June and 2 October. On average, the reservoir was releasing energy in the form of sensible and latent heat flux during the study period. At the end of the 75 d, the total evaporation was estimated as 490.26 mm. A high correlation was found between the latent heat flux and the wind speed ( R = 0.97). The temperature gradient between air and water was positive between 12 and 21 UTC, causing a negative sensible heat flux, and negative during the rest of the day, triggering a positive sensible heat flux. The reservoir acted as a sink of atmospheric CO2 with an average rate of −0.026 mg m −2 s −1 . However, at a daily scale we found an unexpected uptake between 0 and 9 UTC and almost null flux between 13 and 19 UTC. Potential reasons for this result are further discussed. The net radiation was recorded for the same period and water column heat storage was estimated using water temperature profiles. The energy balance closure for the analysed period was 81%. In-water solar spectral downwelling irradiance profiles were measured with a new device allowing measurements independent of the solar zenith angle, which enabled the computation of the attenuation coefficient of light in the water column. The average attenuation coefficient for the photosynthetically active radiation spectral region varied from 0.849 ± 0.025 m −1 on 30 July to 1.459 ± 0.007 m −1 on 25 September.